Efikasi Diri, Dukungan Sosial dan Penyesuaian Diri Dalam Belajar - Mahmudi, Moh.Hadi; Suroso, Suroso (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract, This study aimed to test whether there is a relationshipÂ  of self-efficacy and social support with students adjustment inÂ  learning. Subjects were 123 students of class VII students consisting of 62 men and 61 women taken at random in SMP Negeri 1 Larangan kabupaten Pamekasan. The results of multiple regression analysis obtained for R = 0.759 ; F = 81.600 , p = 0.000 ( p < 0.01 ) . The results of the analysis of this data show self-efficacy and social support of parents jointly associated with the adjustment of students in learning , at 56.9 % . Results of correlation analysis of self-efficacy with self-adjustment of students in the learning acquired partial r = 0.430 ; t = 5.222 and p = 0.000 ( p < 0.01 ) . These data show there is a positive correlation between self-efficacy with self-adjustment of students in learning , with effective contribution of 24.22% . The results of correlation analysis of parent social support with students adjustment in learning obtained partial r = 0.580 ; t = 7.799 and p = 0.000 ( p < 0.01 ) . These data show there is a positive correlation between social support of parents with students adjustment in learning, the effective contribution of 32.68%.Keyword : Adjustment, self efficacy, social support of parents.